A SpA+LukAB vaccine targeting Staphylococcus aureus evasion factors restricts infection in two minipig infection models - Jan T. Poolman; Victor J. Torres; Dominique Missiakas; Suzanne P. M. Welten; Jeffrey Fernandez; Ashley L. DuMont; Anna O’Keeffe; Sergey R. Konstantinov; Brian Morrow; Peter Burghout; Jan Grijpstra; Miranda M. C. van Beers; et al. (npj Vaccines)
Abstract Staphylococcus aureus is a major cause of bacterial infection-related deaths. Increasing antimicrobial resistance highlights the urgent need for effective preventative strategies. Antibody-mediated opsonophagocytosis, the key mechanism for protection against S. aureus, is disabled by critical virulence factors such as Staphylococcal protein A (SpA) and leukocidin AB (LukAB). In our study, we combined genetically detoxified vaccine candidates SpA* and LukAB RARPR-33 with a TH1 adjuvant aiming to restore host antibody functionality. To evaluate these vaccine candidates, we developed both surgical site infection (SSI) and superficial wound infection (SWI) models in minipigs. Our results showed a significant reduction in bacterial load and systemic dissemination in the SSI model, while skin infection severity was markedly decreased after intradermal immunization in the SWI model. This study introduces a novel S. aureus vaccine strategy by targeting immune evasion factors SpA and LukAB, utilizing potent TH1 adjuvants, and employing minipig challenge models.